COMPARISON OF MINERAL TRIOXIDE AGGREGATE, ENDOSEQUENCE ROOT REPAIR MATERIAL, AND BIODENTINE USED FOR REPAIRING ROOT PERFORATIONS: A SYSTEMATIC REVIEW - Faisal Alghamdi; Esraa Aljahdali (Cumhuriyet University, 2019)
The root perforation, in spite of being taken as a challenging accident in root canal treatment, has to offer favorable results when exposed to appropriate therapeutic conduct and the usage of materials that have convenient properties. The aim of the current review is to collect all updated and available studies including imperative information concerning the use of Mineral trioxide aggregate, EndoSequence root repair material and Biodentine in the treatment of root perforation approaching some of the key properties for treatment success. A search was performed in the two automated databases (Google Scholar and PubMed use English-language literature) for this systematic review, using specific inclusion and exclusion criteria and keywords. The electronic search was done in December 2018 and update in June 2019. Our inquiry uncovered Twenty-two studies that met the exclusion and inclusion criteria. These studies investigated the use of MTA, EndoSequence ERRM and Biodentine in the root perforation that happened during the endodontic treatment. It was confirmed that there is no unanimity in this review concerning the material that shows the best characteristics, once none of the materials discussed had all the major properties higher than the others, this way it is required the enforcement of further studies aimed at selecting the best characteristics of the material suggested in the root perforation treatment.